Numerical analysis of heat transfer in human head - Kamangar, Sarfaraz; Khan, Mohammad Anas; Badruddin, Irfan Anjum; Yunus Khan, T.M.; Nik-Ghazali, Nik Nazri (Springer Verlag (Germany), 2019)
An investigation of heat transfer in human head is carried out by using finite element method. The head is modeled with different tissues having varying physical properties. The current work is focused to simulate the effect of various physical and geometrical parameters such as ambient temperature, heat transfer coefficient and variation in the thickness of different tissue layers of human head. The effect of presence of hair on human head is also investigated. It is found that the deep brain temperature remains almost constant whereas a small variation occurs in the other layers with respect to varying environmental and geometrical parameters. © 2019, KSME & Springer.